Current and conductance modulation at elevated temperature in silicon and InAs-based spin field-effect transistors - Dmitri Osintsev; Viktor Sverdlov; Alexander Makarov; Siegfried Selberherr (Universiti Kebangsaan Malaysia, 2013)
Spin field-effect transistors (SpinFETs) are promising candidates for future integrated microelectronic circuits. A SpinFET is composed of two ferromagnetic contacts (source and drain), which sandwich a semiconductor channel. Current modulation is achieved by electrically tuning the gate voltage dependent strength of the spin-orbit interaction in the semiconductor region. We investigated the properties of SpinFETs for various parameters - the band mismatch, the barrier height between the contacts and the channel and the strength of the spin-orbit coupling, for various temperatures. We demonstrated that the creation of Schottky barriers between the channel and the contacts guarantees a pronounced modulation of the magnetoresistance sufficient to open a possibility to operate SpinFETs at room temperature. We also demonstrated that silicon fins with [100] orientation exhibit a stronger dependence on the value of the spin-orbit interaction and are thus preferable for practical realization of silicon-based SpinFETs.